Sex differentiation of channel catfish gonads: Normal development and effects of temperature - Patiño, R; Davis, K; Schoore, J; Uguz, C; Strüssmann, C; Parker, N; Simco, B; Goudie, C (1996)
Channel catfish have an XX female-XY male sex determination system. Although genetic males of this species are readily feminized with exogenous steroid, the pattern of gonadal sex differentiation and the effect of temperature on genetic sex determination are unknown. To document the pattern of gonadal sex differentiation, catfish from a mixed-sex progeny (XX female-XY male cross), known XY males (XX female-YY male cross), and steroid sex-reversed (XY) females were reared at 28°C and collected for histological analysis from Day 7 to Day 90 postfertilization. No signs of gonadal sex differentiation were detected from Day 7 to Day 16. On Day 19, about half the fish from the mixed-sex population as well as the sex- reversed females had gonads with proximal and distal tissue outgrowths. These outgrowths eventually fused to form an ovarian cavity. Germ cell meiosis in these gonads was first detected on Day 22 and growing ovarian follicles were seen at later stages. Thus, ovarian differentiation began about Day 19. Although presumptive testes lose their sensitivity to feminizing steroids about Day 19, the gonads of known males and of putative males from the mixed-sex population showed no clear signs of sex differentiation up to Day 90. Thus, the prolonged temporal dissociation between testicular commitment and differentiation indicates that these two events may be mediated by separate stimuli. To determine the effects of temperature on sex determination, fish of a mixed-sex population were reared at 27°C until Day 10; at 20°, 27°, or 34°C from Day 10 to Day 24; and then at 27°C until Day 102 when sex ratios and gonadal histology were determined. The sex ratio was significantly skewed toward females in fish treated at 34°C (1 male:1.68 female; P < 0.01) but no effects were seen at 20° or 27°C. This observation suggests that genetic and temperature- dependent mechanisms of sex determination are both functional in channel catfish and that this phenomenon is more widespread in fishes than previously believed. The testes of the Day 102 males examined had developed positive histological signs of sex differentiation, suggesting that testicular formation in channel catfish normally starts between Day 90 and 102.